Comparison of morphometric and histological properties of testicles and sperm production in breeding bulls with different reaction to stress - Chernenko, Oleksandr; Chernenko, O. M.; Chernenko, Oleksandr Mikolajovich; Chernenko, O.; Chernenko, Oleksandr M.; Chernenko, A.; Черненко, Олександр Миколайович; Pryshedko, V. M.; Pryshedko, Vladimir M.; Pryshedko, V.; Prishedko, V.; Pryshed’ko, Vladimir; et al. (Croatian Veterinary Institute, Zagreb, 2022)
The aim of this study was to determine the association between bulls with different resistance to stress and the morphological and histological characteristics of the testicles and epididymis, and quantitative and qualitative indicators of sperm production for the first three years of their use on a regional breeding holding. Based on cortisol concentrations before and after stress, bulls were divided into two groups, the first with higher stress resistance (n=9) and the second with lower stress resistance (n=7). Animals of the second group had a 11.9% higher incidence of rejected sperm due to poor quality. Animals with a higher stress resistance had a 16.6% larger relative area of the seminal canals, higher weight of the testicles, larger size of the testicles, in both length and width, higher weight of the testicular appendage, and better development of the two testicular appendages. The adaptive capacity of breeding bulls should be selectively improved to evaluate their stress resistance according to the cortisol concentrations before and one hour after stress. When completing herds, it is preferable to use animals with a higher resistance to stress. Метою даного дослідження було визначити зв'язок між ступенем резистентності до стресу бугаїв-плідників та їх морфологічними і гістологічними характеристиками сім'яників та придатків сім'яників, а також кількісними та якісними показниками спермопродукції за перші три роки їх використання у регіональному племрепродукторі. За концентрацією кортизолу до і після стресу, бугаї були розділені на дві групи: перша з вищою стресостійкістю (n=9) і друга - з нижчою стресостійкістю (n=7). Тварини другої групи мали на 11,9% вищу частоту відбракованої сперми через низьку якість. Тварини з вищою стресостійкістю мали на 16,6% більшу відносну площу сім'яних канальців, більшу вагу та розмір сім'яників, як в довжину, так і в ширину, більшу вагу придатка сім'яника, і кращий розвиток обох придатків сім'яників. Адаптаційну здатність бугаїв-плідників слід вибірково покращувати за оцінкою їх стресостійкості відповідно до концентрації кортизолу до та через годину після стресового навантаження. При комплектуванні стада бажано використовувати тварин з вищою стійкістю до стресу.
Порівняння морфометричних і гістологічних властивостей сім'яників та спермопродукції бугаїв-плідників з різною реакцією на стрес
Черненко Олександр Миколайович https://orcid.org/0000-0002-8829-3148 Пришедько Володимир Михайлович https://orcid.org/0000-0002-7324-5458 Черненко Олена Іванівна https://orcid.org/0000-0002-5951-6576 Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813 Шульженко Наталія Миколаївна https://orcid.org/0000-0002-8560-4350
Keywords: sperm quality; якість сперми; bulls; бугайці; morphological and histological characteristics of the testicles; морфологічні та гістологічна характеристика сім'яників